[tex]3\sqrt{7}(\sqrt{7}-x)-2x(x^2-2\sqrt{7})=3\sqrt{7}\cdot\sqrt{7}-3\sqrt{7}x-2x\cdot x^2-2x\cdot(-2\sqrt{7})=\\\\=3\cdot7-3\sqrt{7}x-2x^3+4\sqrt{7}x=21+\sqrt{7}x-2x^3\\\\Obliczam\ \ warto\'s\'c\ \ wyra\.zenia\ \ dla\ \ x=-\sqrt{7}\\\\21+\sqrt{7}x-2x^3=21+\sqrt{7}\cdot(-\sqrt{7})-2\cdot(-\sqrt{7})^3=21-7-2\cdot(-\sqrt{343})=\\\\=14+2\cdot\sqrt{343}=14+2\cdot\sqrt{49\cdot7}=14+2\cdot\sqrt{49}\cdot\sqrt{7}=14+2\cdot7\sqrt{7}=\\\\=14+14\sqrt{7}=14\sqrt{7}+14[/tex]
[tex]Odp.\ \ Warto\'s\'c\ \ wyra\.zenia\ \ jest\ \ r\'owna\ \ 14\sqrt{7}+14[/tex]